The development of switchable thulium doped fiber laser in 2-micronmeter wavelength region / Aisah Muhamad - Aisah, Muhamad (2017)
Thulium doped fiber (TDF) laser is widely known for its ability to broaden its spectrum emission until 2.0 μm by with the range of wavelength between 1800 until 2100 nm which is almost into the infrared region. Laser diodes with the maximum power of 220 mW emission at the wavelength of 1550 nm will be used to provide the input power to the TDF with forward pumping configuration. A single pass and double pass configurations of TDF amplifier were implemented. In this study, the input test signal used are in the form of high signal (close to saturation) and low signal which are 0 dBm and -20 dBm respectively. The double pass configuration was able to give a high gain with low noise figure with the value of 28 dB and 3.48 dB respectively. Thus, it makes the efficiency of the amplifier from double pass amplification higher than the single pass configuration with the difference of 7.83%. The TDF laser has simply come from a closed laser cavity configuration with a laser diode at the wavelength of 1550 nm as the pump. The TDF laser was emitted at the wavelength of 1961 nm with a narrow 3-dB bandwidth of approximately 0.04 nm. A switchable TDF laser was proposed by employing an arrayed waveguide grating (AWG) as the wavelength selective mechanism. The emitted laser that can be tuned within the range of 17.27 nm in the region of 2 m. The interval spacing between the adjacent channels is approximately 100 GHz where every laser emission at the selected wavelength is able to produce an acceptable SMSR value, which is within 58.75 dB and narrow band of 3-dB bandwidth with approximately of 0.06 nm. The research output can be used in many applications such as in telecommunication system, medical appliances and remote sensing.